Dynamic Simulation Study on Alternative Marine Drilling Riser Materials in the Deep-Waters of the Norwegian Sea - Wareberg, Kristoffer (University of Stavanger, Norway, 2017)
Master's thesis in Petroleum engineering In the pursuit of more oil and gas to meet the growing demand and replace the declining production, the offshore industry is pushed to invest, explore and drill new wells in deeper waters with harsh environments and with a possibility of HPHT wells and sour well flows. Drilling risers with strength and corrosion resistance capable of handling these extreme conditions are accordingly required. As the water depth increases, the length and weight of the riser might lead to problems in terms of; increased loadings on the handling equipment and tensioner system, as well as storage and transportation limitations. Today, the conventional riser material is steel. Steel is a strong and relatively cheap material. However, it is heavy and not very corrosion resistant. Hence, the industry has turned its focus to lighter alternative materials. Aluminum and titanium risers with their light weight, high strength-to-weight ratio and good corrosion resistance are potential candidates to substitute the heavy steel risers. In order to assess aluminum and titanium as alternative materials in riser design and determine if they are suitable for operations in the harsh environment in the Norwegian Sea, simulation studies in OrcaFlex has been conducted. The environmental data used in the simulations are from the Aasta Hansteen gas field, in an area of the Norwegian Sea where the water depth is about 1200 m. The output from the simulation software are compared with the ISO standard 13624 to find the maximum flex joint angles and von Mises stress. The results from the dynamic simulations show that wave height and drilling fluid density influences the effective tension, flex joint angles and the von Mises stress. The applied top tension proves to have the biggest impact on the results, and should be closely considered during the design phase. Aluminum and titanium both proves to fulfill the given design parameters, and can potentially be an alternative to the conventional steel riser in drilling ...